Insular projections to the parahippocampal region in the rat. Issue 9 (23rd February 2015) - Mathiasen, Mathias L.; Hansen, Lilliane; Witter, Menno P.
ABSTRACT: The insular cortex is involved in the perception of interoceptive signals, coding of emotional and affective states, and processing information from gustatory, olfactory, auditory, somatosensory, and nociceptive modalities. This information represents an important component of episodic memory, mediated by the parahippocampal‐hippocampal region. A comprehensive description of insular projections to the latter region is lacking. Previous studies reported that insular projections do not target any of the subdivisions in the hippocampal formation (the dentate gyus, the cornu ammonis [CA] fields 1, 2, and 3 and the subiculum), but, in contrast, target the parahippocampal region (perirhinal, postrhinal, lateral and medial entorhinal cortices, and pre‐ and parasubiculum). The present study examined the topographical and laminar organization of insular projections to the parahippocampal region in the rat with the use of anterograde tracing. Notably, our results corroborated the absence of hippocampal projections. We further showed that the perirhinal and the lateral entorhinal cortices received extensive projections from the insular cortex, primarily from its agranular areas. With the exception of a weak projection to the postrhinal cortex, projections to the remaining parahippocampal areas were either absent or very sparse. The projections to the lateral entorhinal cortex displayed a preference for the deep layers of its most lateral subdivisions, known also to receive hippocampal inputs. Projections to the perirhinal cortex primarily targeted the superficial layers with a preference for its ventral subdivision, referred to as area 35. Our findings indicate that only processed information, reflecting emotional and affective states, but not primary gustatory and viscerosensory information, has direct access to the parahippocampal‐hippocampal system. J. Comp. Neurol. 523:1379–1398, 2015. © 2015 Wiley Periodicals, Inc. Abstract : Using anterograde tract‐tracing techniques, the projections from the insular cortex to the parahippocampal region in the rat were visualized. Projections originate predominantly from agranular portions of the insular cortex and display a marked preference for perirhinal superficial layers and lateral entorhinal deep layers.